The Functional Characterization of TcMyoF Implicates a Family of Cytostome-Cytopharynx Targeted Myosins as Integral to the Endocytic Machinery of Trypanosoma cruzi - Nathan Michael Chasen (American Society for Microbiology, 2020)
ABSTRACT Of the pathogenic trypanosomatids, Trypanosoma cruzi alone retains an ancient feeding apparatus known as the cytostome-cytopharynx complex (SPC) that it uses as its primary mode of endocytosis in a manner akin to its free-living kinetoplastid relatives who capture and eat bacterial prey via this endocytic organelle. In a recent report, we began the process of dissecting how this organelle functions by identifying the first SPC-specific proteins in T. cruzi. Here, we continued these studies and report on the identification of the first enzymatic component of the SPC, a previously identified orphan myosin motor (MyoF) specifically targeted to the SPC. We overexpressed MyoF as a dominant-negative mutant, resulting in parasites that, although viable, were completely deficient in measurable endocytosis in vitro. To our surprise, however, a full deletion of MyoF demonstrated only a decrease in the overall rate of endocytosis, potentially indicative of redundant myosin motors at work. Thereupon, we identified three additional orphan myosin motors, two of which (MyoB and MyoE) were targeted to the preoral ridge region adjacent to the cytostome entrance and another (MyoC) which was targeted to the cytopharynx tubular structure similar to that of MyoF. Additionally, we show that the C-terminal tails of each myosin are sufficient for targeting a fluorescent reporter to SPC subregions. This work highlights a potential mechanism used by the SPC to drive the inward flow of material for digestion and unveils a new level of overlapping complexity in this system with four distinct myosin isoforms targeted to this feeding structure. IMPORTANCE The parasite Trypanosoma cruzi is the etiological agent of Chagas disease and chronically infects upwards of 7 million people in the Americas. Current diagnostics and treatments remain grossly inadequate due, in part, to our general lack of understanding of this parasite’s basic biology. One aspect that has resisted detailed scrutiny is the mechanism employed by this parasite to extract nutrient resources from the radically different environments that it encounters as it transitions between its invertebrate and mammalian hosts. These parasites engulf food via a tubular invagination of its membrane, a strategy used by many protozoan species, but how this structure is formed or functions mechanistically remains a complete mystery. The significance of our research is in the identification of the mechanistic underpinnings of this feeding organelle that may bring to light new potential therapeutic targets to impede parasite feeding and thus halt the spread of this deadly human pathogen.